As relações de salário eficiência e produtividade indústria de transformação brasileira 2007 a 2019 - Carvalho, Vitor Hugo de Souza (Brasil, 2022)
The objective of this study is to analyze the relations of the Theory of Wage Efficiency and Work Productivity in the Brazilian manufacturing industry in the period 2007-2019. The Manufacturing Industry is responsible for 11.30% of the country's GDP in the first quarter of 2021, thus being one of the main activities in the country with one of the largest masses of workers in the activity, in more than 8 people in 2022 The study is segmented into 4 parts. The first part analyzes the labor productivity of the period, followed by a discussion of the relation between them. Finally, tests that verify relationships through a Pearson's correlation matrix. The results show a strong Correlation between personnel costs and expenses, representing the Salary Mass and the Productivity in the period, indicating that the Theory of Wage Efficiency can be observed in the Brazilian Manufacturing Industry.